The Mode of Reflexive Practice among Young Indonesian Creative Workers in the Time of COVID-19 - Sutopo, Oki Rahadianto; Wibawanto, Gregorius Ragil; Utomo, Ariane; Beta, Annisa R; Kurnia, Novi (2022)
This article examines reflexive practice among young creative workers in Yogyakarta, Indonesia, during COVID-19. Since March 2020, the COVID-19 pandemic has unleashed a series of relentless and overlapping crises across the Indonesian archipelago. In urban centres across Indonesia, the arts and creative sectors are among the key economic sectors severely afflicted by the pandemic. COVID-19 implies a lot more than the loss of income and livelihoods. Mobility restrictions, gig cancellations, venue closures, all entail the loss of connections, opportunities, and creative outlets. Yet despite such uncertain conditions, young creative workers remain reflexively creative in order to survive in everyday life. Building upon interviews and focus-group discussions with young creative workers in Yogyakarta, we found three modes of temporality-based reflexive practice: waiting, doing something and re-learning, which represent young creative workers’ active responses manifested in the practical and contradictory relationship to the diverse possibilities within hierarchical and heterogenous cultural fields in a pandemic era characterised by regular ruptures. The analysis of the data below contributes to the literature on reflexivity and habitus among young creative workers in a time of pandemic. © The Author(s) 2022.